A phenomenological model of vibration signals of epicyclic gearboxes under meshing impact excitations. (15th March 2023) - Liu, Zongyao; Wang, Yadong; Wang, Yutong; Feng, Wei; Zhang, Kun
Abstract: A thorough understanding of the formation mechanism of modulation sidebands in the vibration spectra is helpful to the condition monitoring and fault diagnosis of epicyclic gearboxes. However, these sidebands are commonly very abundant and complicated, which brings a considerable difficulty for spectral analysis. Previous phenomenological models, constructed by a series of cosine functions, provide a concise and effective method to represent the spectral structures of vibration signals, while the meshing impacts are often excluded. Aiming at this issue, a phenomenological model of vibration signals of epicyclic gearboxes under meshing impact excitations is proposed in this paper. In the present work, the impact force when gear teeth are engaged into meshing is calculated. Then the effects of meshing impacts on the vibration signals are investigated, and vibration signals including meshing impacts during the external and internal meshing process are simulated. After that, a phenomenological model is established with meshing impacts considered, and the spectral structures of the phenomenological model of epicyclic gearboxes in different health conditions are deduced using Fourier series analysis. In addition, since both the angular shift and the meshing impact can influence the vibration signals of epicyclic gearboxes largely, this paper makes a comparison between these two issues, and the comparison results show that the angular shift may affect the spectrum more seriously. Finally, the established phenomenological model is validated with the experimental vibration data from a test rig, and it is concluded that the proposed model is helpful to the condition monitoring and fault diagnosis of epicyclic gearboxes through the verification.